Proteomic profile of dormancy within Staphylococcus epidermidis biofilms using iTRAQ and label-free strategies - Carvalhais, Virgínia Maria Dinis (2015)
Staphylococcus epidermidis is an important nosocomial bacterium among carriers of indwelling medical devices, since it has a strong ability to form biofilms. The presence of dormant bacteria within a biofilm is one of the factors that contribute to biofilm antibiotic tolerance and immune evasion. Here, we provide a detailed characterization of the quantitative proteomic profile of S. epidermidis biofilms with different proportions of dormant bacteria. A total of 427 and 409 proteins were identified by label-free and label-based quantitative methodologies, respectively. From these, 29 proteins were found to be differentially expressed between S. epidermidis biofilms with prevented and induced dormancy. Proteins overexpressed in S. epidermidis with prevented dormancy were associated with ribosome synthesis pathway, which reflects the metabolic state of dormant bacteria. In the opposite, underexpressed proteins were related to catalytic activity and ion binding, with involvement in purine, arginine, and proline metabolism. Additionally, GTPase activity seems to be enhanced in S. epidermidis biofilm with induced dormancy. The role of magnesium in dormancy modulation was further investigated with bioinformatics tool based in predicted interactions. The main molecular function of proteins, which strongly interact with magnesium, was nucleic acid binding. Different proteomic strategies allowed to obtain similar results and evidenced that prevented dormancy led to an expression of a markedly different repertoire of proteins in comparison to the one of dormant biofilms.